Front Cover Jurnal Sisfokom (Sistem Informasi dan Komputer) Vol. 9 No. 2 Juli 2020 - Editor in Chief Sisfokom (ISB Atma Luhur, 2020)
This article contains front-matter of Jurnal Sisfokom (Sistem Informasi dan Komputer), Volume 9 Number 2 - July 2020, which includes a cover page, title page, editorial team, and table of contents.